7+4(3x-5)=9-3(2x+1)

Simple and best practice solution for 7+4(3x-5)=9-3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+4(3x-5)=9-3(2x+1) equation:


Simplifying
7 + 4(3x + -5) = 9 + -3(2x + 1)

Reorder the terms:
7 + 4(-5 + 3x) = 9 + -3(2x + 1)
7 + (-5 * 4 + 3x * 4) = 9 + -3(2x + 1)
7 + (-20 + 12x) = 9 + -3(2x + 1)

Combine like terms: 7 + -20 = -13
-13 + 12x = 9 + -3(2x + 1)

Reorder the terms:
-13 + 12x = 9 + -3(1 + 2x)
-13 + 12x = 9 + (1 * -3 + 2x * -3)
-13 + 12x = 9 + (-3 + -6x)

Combine like terms: 9 + -3 = 6
-13 + 12x = 6 + -6x

Solving
-13 + 12x = 6 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-13 + 12x + 6x = 6 + -6x + 6x

Combine like terms: 12x + 6x = 18x
-13 + 18x = 6 + -6x + 6x

Combine like terms: -6x + 6x = 0
-13 + 18x = 6 + 0
-13 + 18x = 6

Add '13' to each side of the equation.
-13 + 13 + 18x = 6 + 13

Combine like terms: -13 + 13 = 0
0 + 18x = 6 + 13
18x = 6 + 13

Combine like terms: 6 + 13 = 19
18x = 19

Divide each side by '18'.
x = 1.055555556

Simplifying
x = 1.055555556

See similar equations:

| W=4w | | 2000=225(x+3.5) | | 7-4(3x-5)=9-3(2x+1) | | 0=675x-16250-x^2 | | 9x^2+48x+140=0 | | 2x^2-13x+4.25=0 | | 360=2lw+2lh+2wh | | 7+4(3x-5)=9-3(2x-1) | | 3+2x=7x-47 | | 7-4(3x-5)=9-3(2x-1) | | 2x^2+10x=180 | | 14.2-d=9.2 | | 2.9(f+4)-1.22=16.18 | | -2.12(w+-4)=12.72 | | -4r^2+21r=r+13 | | 45=6x+3x+9 | | 140/u=28 | | 4x^2-1/16=0 | | 11(y-881)+234=806 | | R=8x^2+2x-9 | | 17+2= | | 4x^2-1/6=0 | | 6.7-j=6.8 | | 9x-3=6x+5 | | X^2+1=4+2x-x^2 | | M/5+(3m-6)/2=2m-6 | | 2.8(t-6)+1=9.4 | | 3(s+1.78)=11.67 | | 183-p=851 | | ((24x)/(884-24x))=1 | | 10(b+235)=760 | | 3g+6=18 |

Equations solver categories